Workplace Diversity and Inclusion: Strategies for Effective Implementation and Benefits to Organizational Culture - Leuhery, Ferdy; Salu Padang, Nely; Karyono, Karyono; Puspitasari, Dewi; Judijanto, Loso (Dinasti Publisher, 2024)
This article reviews literature on workplace diversity and inclusion, emphasizing strategies for effective implementation and the resulting benefits to organizational culture. The importance of diversity and inclusion in fostering innovation, enhancing employee engagement, and improving organizational performance has been widely recognized. This review synthesizes findings from various studies to identify best practices and strategies for promoting diversity and inclusion, including leadership commitment, inclusive policies, diversity training, and employee resource groups. Additionally, the article explores the positive impacts of diversity and inclusion on organizational culture, such as increased creativity, better decision-making, and a more supportive work environment. The findings suggest that organizations that effectively implement diversity and inclusion strategies not only benefit from a more dynamic and innovative workforce but also create a culture of belonging and respect that can drive long-term success. This article aims to provide a comprehensive overview for practitioners and scholars interested in enhancing workplace diversity and inclusion.